2000
DOI: 10.1002/dei.68
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction and early language development in deaf children

Abstract: The last decade has witnessed a steady increase in research on interaction between young deaf children and their parents. As a result we are beginning to have a clearer idea of some of the ways in which these interactions differ from those between hearing children and their parents and how such differences may affect deaf children's early language development. In this article I want to reflect upon some of the main findings of the last decade and to speculate about the research issues that will be important in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…This concerned the relative proportions of responsive, spontaneous and elicited episodes between 12 and 18 months. Previous studies (Harris & Mohay, 1997;Harris, 2000) have shown that responsive episodes were the most frequent type of episode at 18 months of age. The present study showed that this was also true at 9 and 12 months of age.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This concerned the relative proportions of responsive, spontaneous and elicited episodes between 12 and 18 months. Previous studies (Harris & Mohay, 1997;Harris, 2000) have shown that responsive episodes were the most frequent type of episode at 18 months of age. The present study showed that this was also true at 9 and 12 months of age.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies (Harris & Mohay, 1997;Harris, 2000;Harris & Chasin, 2005) have looked at the nature of children's switches of visual attention towards their mothers. Harris & Mohay (1997) divided switches of attention into one of three mutually exclusive categories.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesis‐3 is that the sign language from caregivers provides specific socializing and scaffolding behavior that may play a role over and above the Deaf infant’s absence of hearing (H‐1) or their increased experience with attending to visual bodily signals (H‐2). Hypothesis‐3 holds that Deaf parents actively engage in specific communicative and linguistic behaviors that are highly adaptive in the Deaf culture and may scaffold gaze‐following development (Corina & Singleton, ; Harris, ; Lieberman, Hatrak, & Mayberry, ; Meadow‐Orlans et al, ; Spencer, ).…”
Section: Discussionmentioning
confidence: 99%
“…A deaf child needs to look at their caregiver to get linguistic input, but they also need to look at objects to learn about the world. Across a number of studies observing deaf caregiver–deaf infant dyads (based in several different countries and using natural signed languages), a repertoire of “visually responsive” culturally embedded behaviors has been documented among caregivers (Erting, Prezioso, & Hynes, 1990; Harris, 2000; Koester, Brooks, & Traci, 2000; Waxman & Spencer, 1997). To summarize, deaf caregivers: (a) use visual or tactile signals to elicit their child’s visual attention (through a hand‐wave or physical touch), (b) displace their signing to be within the child’s line of sight (as they look at the object), (c) use longer wait times before producing child‐directed language (i.e., waiting until the child independently looks to the caregiver before starting to sign), and (d) use greater persistence to successfully gain and redirect the child’s attention (see Loots & Devise, 2003, for a more detailed summary of deaf caregiver–infant dyad behaviors).…”
Section: Visual Attention: Biological and Social Implicationsmentioning
confidence: 99%